High-mobility low-contact-resistance target material for solar cell and thin film preparation method

By using composite targets doped with high-purity indium oxide with nano-scale metal powder, wide bandgap and high-priced metal elements in heterojunction batteries, the contact performance of the silver gate and the ITO layer is optimized, the contact resistance problem is solved, and the film preparation with high mobility and low contact resistance is achieved, which improves battery performance and production efficiency.

CN119822789APending Publication Date: 2025-04-15WUHU YINGRI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510030143.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the contact resistance between the ITO and the silver gate in heterojunction batteries, and the commonly used methods are complex, costly, and have high environmental and safety requirements, making it difficult to achieve uniformity and stability in large-scale production.

Method used

High-purity indium oxide is used to composite dopate with nano-scale metal powder, wide-bandgap metal elements and high-priced metal elements, and PVD film preparation is combined with specific process parameters to optimize the contact performance of the silver gate and the ITO layer.

Benefits of technology

It realizes a film with high mobility and low contact resistance, simplifies production processes, reduces equipment requirements, improves the controllability of production efficiency and product quality, and improves the performance and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005233908040000061
    Figure BDA0005233908040000061
  • Figure BDA0005233908040000081
    Figure BDA0005233908040000081
  • Figure BDA0005233908040000093
    Figure BDA0005233908040000093
Patent Text Reader

Abstract

The invention relates to the technical field of target materials, and provides a high-mobility and low-contact-resistance target material for a solar cell and a thin film preparation method, and the high-mobility and low-contact-resistance target material for the solar cell is prepared by using one or two metal oxides of nanoscale metal powder Ag, Cu and A, one or two metal oxides of wide-band-gap elements T , Ga and Zn, one or two metal oxides of high-valence elements Zr, W and Mo, one or two metal oxides of high-valence elements T , Ga and Zn and one or two metal oxides of high-valence elements Zr, W and Mo. According to the preparation method, a PVD thin film preparation process is optimized on the basis of obtaining a high-density target material by performing composite doping with high-purity indium oxide according to different proportions, and a metal oxide thin film with high mobility and low contact resistance for a window layer of a solar cell is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of target materials, and in particular to a high-mobility and low-contact-resistance target material for solar cells and a method for preparing a thin film. Background Art

[0002] As a high-efficiency photovoltaic cell, the heterojunction cell has a unique structure and excellent performance. It is usually composed of a variety of different semiconductor materials. For example, in the common silicon-based heterojunction cell, amorphous silicon and crystalline silicon are combined to form a heterojunction structure. This structure can effectively separate photogenerated carriers and reduce the recombination probability of carriers, thereby improving the photoelectric conversion efficiency of the cell. In practical applications, heterojunction cells have shown high open circuit voltage and short circuit current density, which makes them have broad application prospects in the field of photovoltaic power generation and become one of the current research hotspots.

[0003] In the structure of heterojunction batteries, ITO (indium tin oxide), silver grid and semiconductor silicon layer are important components, but there is a non-negligible contact resistance problem between them. When current passes through these interfaces, due to factors such as differences in the work function of the materials, surface states and interface unevenness, charge transfer will be hindered, resulting in contact resistance. This contact resistance will increase the series resistance of the battery, thereby reducing the battery's fill factor and photoelectric conversion efficiency. For example, in a high temperature and high humidity environment, chemical reactions or physical changes may occur at the interface, further deteriorating the contact resistance and affecting the long-term stability and performance reliability of the battery.

[0004] In order to solve the problem of contact resistance between ITO and silver grid, a variety of methods have been developed. A common method is to insert an ultra-thin buffer layer between ITO and silver grid, such as using metal oxide or nitride materials. This buffer layer can adjust the work function of the interface, reduce the band bending at the interface, and thus reduce the contact resistance. In addition, by plasma treatment or chemical modification of the ITO surface to improve its surface chemical activity and roughness, the contact performance between ITO and silver grid can also be enhanced and the contact resistance can be reduced. In addition, optimizing the preparation process of the silver grid, such as controlling the deposition rate, temperature and pressure of silver to form a more dense and uniform structure, can also help reduce the contact resistance.

[0005] However, although inserting a buffer layer is an effective way to reduce contact resistance, finding a suitable buffer layer material is not simple. On the one hand, the buffer layer material needs to have good compatibility with both ITO and silver grid, and can effectively adjust the work function of the interface and reduce band bending; on the other hand, the buffer layer material also needs to have good stability and will not undergo chemical reactions or physical changes during long-term use. Currently commonly used buffer layer materials such as metal oxides or nitrides still have room for improvement in performance, and their preparation process is also relatively complex and costly.

[0006] Plasma treatment requires precise control of multiple parameters, such as power, gas flow, and treatment time. Different combinations of parameters will have different effects on the ITO surface. For example, too high a power may cause damage to the ITO surface, affecting its conductivity and light transmittance; while improper gas flow and treatment time may not achieve the expected surface modification effect. To find the best combination of parameters, a lot of experiments and optimization are required, which takes a lot of time and resources. In large-scale production, ensuring the uniformity of plasma treatment is a key difficulty. Since the distribution of plasma may be affected by factors such as equipment structure and gas flow characteristics, uneven treatment is prone to occur, resulting in differences in the chemical activity and roughness of the ITO surface in different areas, which in turn affects the consistency of contact performance with the silver grid and reduces the overall performance and stability of the battery.

[0007] The control of reaction conditions in the chemical modification process is relatively complex, requiring strict experimental conditions and operating specifications, which increases the difficulty of large-scale production. In addition, many chemical modification reagents are toxic and corrosive, posing a threat to the environment and the safety of operators. At the same time, during the production process, strict protective measures and waste disposal methods need to be taken, which not only increases production costs, but also puts higher requirements on the production environment and safety management.

[0008] Although optimizing the preparation process of the silver grid can also reduce the contact resistance, this requires high-precision equipment and advanced process technology. During the silver deposition process, parameters such as deposition rate, temperature and pressure need to be precisely controlled to ensure the density and uniformity of the silver grid. At the same time, the pattern design of the silver grid is also very important. Reasonable pattern design can reduce the concentration of current and reduce contact resistance. To achieve high-precision silver grid patterns, advanced lithography, etching or printing technologies are required. These technologies are challenging in terms of equipment cost, process complexity and production efficiency.

[0009] Therefore, it is urgent and necessary to develop an oxide target material that is efficient and easy to control to reduce the contact resistance between the silver grid and the ITO layer. Summary of the invention

[0010] In view of this, the purpose of the present invention is to provide a high-mobility and low-contact-resistance target material and a thin film preparation method for solar cells to solve the problems in the background technology.

[0011] Based on the above purpose, the present invention provides a high-mobility and low-contact-resistance target material for solar cells, comprising 86.5-99.75wt% of high-purity indium oxide, the high-purity indium oxide doped with nano-scale metal powder, wide-bandgap metal elements and high-valent metal elements;

[0012] The nano-scale metal powder is doped in the form of oxide, and the doping ratio is 0.05-2wt% by weight;

[0013] The wide bandgap metal element is doped in the form of oxide, and the doping ratio is 0.1-10wt% by weight;

[0014] The high-valent metal element is doped in the form of oxide, and the doping ratio is 0.1-1.5wt% by weight.

[0015] Preferably, the nano-scale metal powder is one or two of Ag, Cu and Al, with a doping ratio of 0.05-0.5wt%.

[0016] Preferably, the wide bandgap element is one or two of Ti, Ga and Zn, with a doping ratio of 0.2-0.5wt%.

[0017] Preferably, the high-valent metal element is one or two of Zr, W and Mo, with a doping ratio of 0.2-0.5wt%.

[0018] A method for preparing a thin film of a high-mobility and low-contact-resistance target material for a solar cell comprises the following steps:

[0019] Step 1: Adjust the base vacuum of the coating machine to 2*10 -4 Pa-9*10 -4 Pa;

[0020] Step 2: Pre-coating. The pre-coating parameters are as follows: power density 1-5W / cm 2 , substrate temperature room temperature 100-250°C, controlled pressure 0.25-1Pa, argon oxygen ratio 1000:1-100:5, hydrogen concentration 0.1-2%, pre-plating time 5-30min;

[0021] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 1-5W / cm 2 , substrate temperature room temperature 100-250°C, controlled pressure 0.25-1Pa, argon oxygen ratio 1000:1-100:5, hydrogen concentration 0.1-2%;

[0022] Step 4: After coating, the film is annealed: the annealing temperature is 150-300°C, and the annealing time is 5-60min.

[0023] Preferably, the vacuum degree of the step is 2*10 -4 Pa-2.5*10 -4 Pa.

[0024] Preferably, the pre-plating time in step 2 is 10-15 minutes.

[0025] Preferably, the coating parameters in step three are as follows: power density 2-3.5 W / cm2, substrate temperature 150-200°C at room temperature, controlled pressure: 0.6-0.9 Pa, argon-oxygen ratio: 100:1-100:2.8, hydrogen concentration: 0.8-1.2%.

[0026] Preferably, the annealing temperature in step 4 is 180-250° C., and the annealing time is 8-30 min.

[0027] Beneficial effects of the present invention: The present invention optimizes the PVD film preparation process on the basis of obtaining a high-density target material by using one or two metal oxides of nano-scale metal powders Ag, Cu, and Al, one or two metal oxides of wide-bandgap elements Ti, Ga, and Zn, one or two metal oxides of high-valent elements Zr, W, and Mo, and high-purity indium oxide for composite doping in different proportions, and obtains a metal oxide film with high mobility and low contact resistance for a solar cell window layer.

[0028] The metal elements selected in the present invention are all elements with good conductivity and similar chemical properties to silver atoms. The doped metal atoms are evenly distributed in the indium oxide lattice during the sintering process. When in contact with the silver grid, based on the affinity and similar chemical properties between silver atoms, better contact effects can be achieved, interface charge transfer barriers can be reduced, and contact resistance can be reduced.

[0029] The metal elements selected in the present invention all have certain oxidizability, and will undergo an oxidative oxygen absorption reaction under specific conditions, which can produce oxygen vacancies in the indium oxide lattice. The presence of oxygen vacancies can increase carrier mobility, making electrons transfer more smoothly in the material, and ultimately achieving a decrease in resistivity, achieving the effect of high mobility and low contact resistance, and providing an effective technical approach for further improving the performance of heterojunction batteries, and promoting the development of heterojunction batteries in a more efficient and stable direction.

[0030] The present invention performs composite doping of metal powder with good electrical conductivity, wide bandgap elements with excellent optical properties, and high-valent elements that can provide holes in a specific proportion. Through the combined effects of different types of doping elements, the contact resistance between the TCO film layer and the silver grid is reduced, and the carrier concentration is simultaneously increased on the basis of improving the film mobility. Moreover, due to the introduction of the wide bandgap metal element, the carrier concentration can be increased without causing a negative impact on the transmittance.

[0031] The present invention dopes metal powder that can reduce contact resistance into the TCO target material, and integrates the process of reducing contact resistance into PVD coating, which not only greatly simplifies the overall production process, but also significantly reduces the complexity of process implementation and the stringent requirements on equipment, effectively improving production efficiency and controllability of product quality. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0033] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0034] The formulation of the high mobility and low contact resistance target material for solar cells in Example 1-5 is as follows:

[0035]

[0036] Example 1-5 A method for preparing a thin film of a high mobility and low contact resistance target material for a solar cell is as follows:

[0037] Example 1

[0038] Step 1: To ensure the performance of the film, use a background vacuum of 2*10 -4 Pa;

[0039] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 1W / cm 2 , substrate temperature room temperature 100 ° C, controlled pressure 0.25 Pa, argon oxygen ratio 1000:1, hydrogen concentration 0.1%, pre-deposition time 5min;

[0040] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 1W / cm 2 , substrate temperature room temperature 100 ° C, controlled pressure 0.25 Pa, argon oxygen ratio 1000:1, hydrogen concentration 0.1%;

[0041] Step 4: The annealing process of the film is as follows: annealing temperature 210°C, annealing time 5 minutes.

[0042] Example 2

[0043] Step 1: To ensure the performance of the film, use a background vacuum of 2*10 -4 Pa;

[0044] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 2W / cm 2 , substrate temperature 150°C, controlled pressure 0.6Pa, argon-oxygen ratio 100:1, hydrogen concentration 0.8%, pre-deposition time 10min;

[0045] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 2W / cm 2 , power density 2W / cm 2 , substrate temperature 150°C, controlled pressure 0.6Pa, argon-oxygen ratio 100:1, hydrogen concentration 0.8%;

[0046] Step 4: The annealing process of the film is as follows: annealing temperature 180°C, annealing time 8 minutes.

[0047] Example 3

[0048] Step 1: To ensure the performance of the film, use a background vacuum of 9*10 -4 Pa;

[0049] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 5W / cm 2 , substrate temperature 250℃, controlled pressure 1Pa, argon-oxygen ratio 100:5, hydrogen concentration 2%, pre-deposition time 30min;

[0050] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 5W / cm2 , substrate temperature 250°C, controlled pressure 1Pa, argon-oxygen ratio 100:5, hydrogen concentration 2%;

[0051] Step 4: The annealing process of the film is as follows: annealing temperature 300°C, annealing time 60min.

[0052] Example 4

[0053] Step 1: To ensure the performance of the film, this patent uses a background vacuum of 2.2*10 -4 Pa;

[0054] Step 2: To further improve the performance of the film, this patent will be pre-plated before the formal coating. The pre-plating parameters are as follows: power density 3W / cm 2 , substrate temperature 180°C, controlled pressure 0.8Pa, argon oxygen ratio 100:1.5, hydrogen concentration 1%, pre-deposition time 12min;

[0055] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 3W / cm 2 , substrate temperature 180°C, controlled pressure 0.8Pa, argon oxygen ratio 100:1.5, hydrogen concentration 1%;

[0056] Step 4: The annealing process of the film is as follows: annealing temperature 210°C, annealing time 20min.

[0057] Example 5

[0058] Step 1: To ensure the performance of the film, use a background vacuum of 2.5*10 -4 Pa;

[0059] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 3.5W / cm 2 , substrate temperature 200°C, controlled pressure 0.9Pa, argon oxygen ratio 100:2.8; hydrogen concentration 1.2%; pre-deposition time 15min;

[0060] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 3.5W / cm 2 , substrate temperature 200°C, controlled pressure 0.9Pa, argon oxygen ratio 100:2.8, hydrogen concentration: 1.2%;

[0061] Step 4: The annealing process of the film is as follows: annealing temperature 250°C, annealing time 30 minutes.

[0062] Comparative Example 1

[0063] Conventional indium tin oxide film with a ratio of indium oxide to tin oxide of 90:10.

[0064] Comparative Example 2

[0065] High mobility indium tin oxide target with an indium oxide to tin oxide ratio of 99:1.

[0066] The test method is as follows: In order to further compare the performance differences between the embodiments, in addition to characterizing the intrinsic performance of each target material, the magnetron sputtering method is also used to verify the coating of each target material.

[0067] The resistivity of the target material is tested using a four-probe resistivity tester; the density of the target material is tested using the drainage method; the square resistance of the film is tested using a four-needle square resistance meter; the thickness of the film is tested using a surface profiler; the transmittance of the film is tested using an ultraviolet spectrophotometer; the carrier concentration and carrier mobility of the film are tested using a Hall effect meter; the contact resistance between the silver grid and the film is tested using the transfer length method (Transfer Length Method) and a Keithley 4200-SCS parameter tester.

[0068] The target intrinsic performance test results are compared as follows:

[0069]

[0070]

[0071] It can be seen from the test results of the intrinsic properties of the target material that the target material prepared by the method according to the present invention has a comparable relative density and a lower resistivity than the comparative example.

[0072] film The comparison of performance test results such as transmittance and resistivity is as follows:

[0073]

[0074] By comparing the data in the above table, it can be seen that the performance of the film has been improved to varying degrees after annealing treatment. This change significantly enhances the feasibility of the relevant products of the present invention in practical applications. At the same time, with the increase of the content of doping elements, the carrier concentration of the film is on the rise, while the transmittance of the film is on the decline. This is because the introduction of doping elements causes an increase in the impurity carriers in the crystal structure of the film, resulting in a certain degree of scattering effect, which ultimately leads to a decrease in the transmittance of the film.

[0075] In addition, the carrier mobility data is closely related to the content of indium oxide in theory. The higher the content of indium oxide, the higher the mobility. However, the present invention relates to Examples 2, 4, and 5, although the content of indium oxide is lower than the traditional 99:1 comparative example 2, its mobility shows a very obvious advantage. On the one hand, this is due to the interaction between the doping elements, which still improves the carrier mobility on the basis of introducing more carriers. On the other hand, during the sintering process, silver absorbs oxygen and oxidizes at high temperature to generate silver oxide. In this process, more oxygen vacancies are generated, thereby further improving the carrier mobility.

[0076] Finally, in the contact resistance part, Example 3 and Comparative Example 2 have similar indium oxide content and the same tin oxide content, but Example 3 shows a lower contact resistance, which shows that the addition of nanosilver particles has an improvement effect on the reduction of contact resistance. At the same time, the change law of the contact resistance of Examples 1-5 did not completely decrease according to the increase in silver content, which may be due to the composite effect of other doping elements. However, the overall trend is still downward, and both Examples 4 and 5 show a contact resistance of less than 10Ω. It can be seen that the addition of silver powder, under the effect of composite doping of multiple elements, shows a significant improvement.

[0077] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

Claims

1. A high mobility and low contact resistance target material for solar cells, characterized in that: The invention comprises 86.5-99.75wt% of high-purity indium oxide, wherein the high-purity indium oxide is doped with nano-scale metal powder, wide-bandgap metal elements and high-valent metal elements; The nano-scale metal powder is doped in the form of oxide, and the doping ratio is 0.05-2wt% by weight; The wide bandgap metal element is doped in the form of oxide, and the doping ratio is 0.1-10wt% by weight; The high-valent metal element is doped in the form of oxide, and the doping ratio is 0.1-1.5wt% by weight.

2. The high mobility and low contact resistance target material for solar cells according to claim 1, characterized in that: The nano-scale metal powder is one or two of Ag, Cu and Al, with a doping ratio of 0.05-0.5wt%.

3. The high mobility and low contact resistance target material for solar cells according to claim 2, characterized in that: The wide bandgap elements are one or two of Ti, Ga and Zn, with a doping ratio of 0.2-0.5 wt%.

4. The high mobility and low contact resistance target material for solar cells according to claim 3, characterized in that: The high-valent metal elements are one or two of Zr, W and Mo, with a doping ratio of 0.2-0.5 wt%.

5. A method for preparing a thin film of a high mobility and low contact resistance target material for solar cells according to claim 4, characterized in that: The following steps are included: Step 1: Adjust the base vacuum of the coating machine to 2*10 -4 Pa-9*10 -4 Pa; Step 2: Pre-coating. The pre-coating parameters are as follows: power density 1-5W / cm 2 , substrate temperature room temperature 100-250°C, controlled pressure 0.25-1Pa, argon oxygen ratio 1000:1-100:5, hydrogen concentration 0.1-2%, pre-plating time 5-30min; Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 1-5W / cm 2 , substrate temperature room temperature 100-250°C, controlled pressure 0.25-1Pa, argon oxygen ratio 1000:1-100:5, hydrogen concentration 0.1-2%; Step 4: After coating, the film is annealed: the annealing temperature is 150-300°C, and the annealing time is 5-60min.

6. The method for preparing a thin film of a high mobility and low contact resistance target material for solar cells according to claim 5, characterized in that: The bottom vacuum degree of the step is 2*10 -4 Pa-2.5*10 -4 Pa.

7. The method for preparing a thin film of a high mobility and low contact resistance target material for solar cells according to claim 5, characterized in that: The pre-plating time in step 2 is 10-15 minutes.

8. The method for preparing a thin film of a high mobility and low contact resistance target material for solar cells according to claim 5, characterized in that: The coating parameters in step 3 are as follows: power density 2-3.5W / cm 2 , substrate temperature is room temperature 150-200°C, controlled pressure: 0.6-0.9 Pa, argon-oxygen ratio: 100:1-100:2.8, hydrogen concentration: 0.8-1.2%.

9. The method for preparing a thin film of a high mobility and low contact resistance target material for solar cells according to claim 5, characterized in that: The annealing temperature in step 4 is 180-250° C., and the annealing time is 8-30 min.